Pengembangan Kawasan Minapolitan Tanggap Bencana Berbasis Sosial Budaya di Kabupaten Serdang Bedagai - R. Hamdani Harahap (Jurnal Agrisep, 2014)
Abstract. This paper is the result of research on Minapolitan area Development Social and Culture-base Disaster Responses in Serdang Bedagai regency. Minapolitan is the center of economy and subsistence which integrated with production speed of potential based on marine and fisheries sector. The data of this research were collected by observation, interview and survey GIS. From the results showed that (1) the facilities and infrastructures in the main of Minapolitan (both in the district of Tanjung Beringin, Perbaungan, Teluk Mengkudu and district of Tebing Tinggi ) have been available, but the quality and quantity still need to be improved especially the condition of the fishing harbor / TPI, means the main roads which connected between the districts included in the main region of Minapolitan. (2) The potential of fisheries still can be improved, by the consideration of sustainable line which need to be developed as an alternative aquaculture saltwater/brackish and fresh water. (3) The quality components supporting the environment of Minapolitan are varies, such as coastal environment occurs reclamation, and mangrove need to be conserved. (4) Development of Minapolitan must consider the balance between regional infrastructure distribution to increase the welfare of society. (5) The most important strategy in building Minapolitan in Serdang Bedagai is to accelerate the construction of physical facilities with the construction of disaster mitigation and build the capacity of society in supporting the development of the Minapolitan itself. The research recommended that all agencies to understand and concern to the issue of Minapolitan and actively involve the community in planning, especially to the manage of natural resources.